Impact of sap-biochar incorporation on controlled release water retention fertilizer (CRWR) towards growth of okras (Abelmoschus Esculentus) - Nureen, Noordin; Suriati, Ghazali; Najahusna, Adnan (Elsevier Ltd, 2018)
The preparation of SAP-biochar as the CRWR coatings material was carried out via solution polymerization technique with introduction of biochar as fillers, in the aim to observe its effect towards Okras. Studies between SAP with and without incorporation of biochar was done for comparison. SEM imaging shows the incorporation of biochar contributes to a porous structure of the SAP hydrogel. The highest WR% and growth height achieved was observed at CRWR SAP-biochar at 75% and 22.3cm respectively. SAP-biochar also showed the lowest percentage of total potassium release of 21.59%. From the results, shows that incorporation of SAP-biochar contributes to a positive effect towards Okras.